Implementation of Village Fund Policy in Improving Community Empowerment Activities in Surabaya City - Nurmala Hayati; Diana Hertati (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study examines the implementation of the Village Fund Policy in Surabaya City in encouraging increased community empowerment activities through physical development. Using a qualitative descriptive research method, this study analyzes the implementation of the Village Fund starting from the planning stage, implementation, mentoring, and evaluation of development activities at the village level. The results show that the utilization of the Village Fund is focused on the development of environmental infrastructure such as drainage channels, paving neighborhood roads, neighborhood association halls, and other social facilities that provide direct benefits to the community. Although the implementation still faces challenges such as work delays due to weather factors, inconsistencies in physical progress, and suboptimal work quality, the Village Fund continues to have a positive impact on community empowerment. This study concludes that the successful implementation of the Village Fund in community empowerment is highly dependent on strengthened planning, effective mentoring, and increased supervision so that development can proceed sustainably and on target.